Influence of targeted observations on short-term forecasts of high-impact weather events in the Mediterranean - J. Campins (Natural Hazards and Earth System Sciences, 2013)
The influence of targeted observations on short-range forecasts is tested over two different periods of PREVIEW (2008) and MEDEX (2009) data targeting field campaigns for a set of Mediterranean high-impact weather events. As targeted observations we have used not only extra radiosondes, but also enhanced satellite data observed in singular vector (SV)-based sensitive regions. Three parallel observing system experiments, based on the High-Resolution Limited-Area Model (HIRLAM) data assimilation and forecast system, have been conducted. Forecasts of the three experiments have been assessed using both verifying analyses for upper-air fields, and surface observations for several meteorological parameters. Furthermore, quantitative precipitation forecasts (QPF) have been objectively verified using the novel feature oriented Structure–Amplitude–Location (SAL) method. The results obtained show that extra radiosondes have an overall positive impact on the forecasts (average improvement of all upper-air variables and vertical levels studied is 3.6%). When in addition to extra radiosonde data also enhanced satellite data are assimilated, the overall forecast skill is almost doubled. However, a distinct behaviour is found between the PREVIEW and MEDEX cases. While for MEDEX cases the improvement is slight, for PREVIEW cases the improvement is significant (average improvements of 1.7% and 8.9%, respectively, for the experiment with enhanced satellite data). It is suggested that this is due to the location of the target areas and the spatial distribution of the composite observing system and to the different atmospheric predictability in these two periods.